The Urgency Of Carbon Accounting Based on Willingness to Pay Carbon Tax - Yenni Mangoting; Patricia Louisa; Vanessa Audrey Yonatan (Universitas Pendidikan Indonesia, 2023)
Main Purpose - The research aims to understand human behavior that plays an important role in reducing CO2 emissions through the concept of WTP which is based on psychological factors, that cover self-esteem, mortality salience, and health consciousness along with demographic factors including income level, knowledge, education, and gender. Method - This study used a survey method, where data was collected through questionnaires that were distributed online to respondents with ages over 17 years. This study collected 150 respondents and data were analyzed using PLS-SEM.Main Findings - The results of the study show that the urgency to legitimize carbon taxes is seen as important by respondents. The average additional burden that respondents are willing to pay is Rp.25.000,- per month. Besides that, all psychological and demographic factors are proven can influence respondents' willingness to pay carbon taxes except for the relationship between income-WTP and self-esteem-health consciousness-WTP.Theory and Practical Implications - The results of this analysis provide insight into the strong will of individuals that can encourage individuals to pay for losses due to carbon emissions based on TMT which will help the regulator to legitimize the implementation of carbon accounting followed by formulating the carbon tax regulations comprehensively as part of global climate governance. Moreover, regulators can focus on the principles of improving the quality of human life rather than just technical issues.Novelty - This research helps to understand the WTP taxes associated with a psychological perspective within the TMT framework.